2011
DOI: 10.1108/00021461111128138
|View full text |Cite
|
Sign up to set email alerts
|

Competing risks models of Farm Service Agency seven‐year direct operating loans

Abstract: Purpose -The purpose of this paper is to apply duration methods to a sample of Farm Service Agency (FSA) direct, seven-year operating loans to identify those variables that influence the time to loan termination and type of termination. Variables include both those known at time of loan origination and those that characterize the changing economic environment over the life of the loan. Also, to examine the impact of various FSA programs promoting policy objectives. Design/methodology/approach -A systematic sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
0
8
1
Order By: Relevance
“…These results at first appear to be somewhat different than those in Dixon et al (2011) whose results were for direct OL loans. Dixon et al found BF loans to be insignificant, while direct loans that were both beginning and socially disadvantaged (BFS) were less likely to be paid in full and, after loan restructuring, were more likely go into default.…”
Section: Ol Modelcontrasting
confidence: 83%
See 3 more Smart Citations
“…These results at first appear to be somewhat different than those in Dixon et al (2011) whose results were for direct OL loans. Dixon et al found BF loans to be insignificant, while direct loans that were both beginning and socially disadvantaged (BFS) were less likely to be paid in full and, after loan restructuring, were more likely go into default.…”
Section: Ol Modelcontrasting
confidence: 83%
“…The method is presented in more detail in Kalbfleisch and Prentice (2002), Dressler and Stokes (2010), and Dixon et al (2011). As opposed to conventional regression methods, duration models accommodate censored observations and time-varying variables routinely, which is relevant for this study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As generally, loan characteristics and borrower financial characteristics are significant variables in determining type of loan outcome (default or paid-in-full) and time to outcome. Changes in the economic environment and farm economy during the life of the loan are significant (Dixon et al, 2011). The staff of DAYBANG will make the evaluation by these two kind of indexes, and highlight the project revenue assessment and other income and expenses during the loan lifetime which can suggest the changes in the economic environment and farm economy during the life of the loan.…”
Section: Swot Analysismentioning
confidence: 99%